The Role of Brand Trust in Mediating the Effects of E-WOM, Content Marketing, and Live Streaming on Generation Z Purchase Decisions on TikTok Shop - Ni Made Padmawati; Ida Bagus Teddy Prianthara (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study investigates the mediating role of brand trust in the relationship between Electronic Word of Mouth (E-WOM), content marketing, and live streaming on Generation Z purchase decisions on TikTok Shop in Bali. The study employed a quantitative approach involving 210 Generation Z consumers in Bali who had previously purchased products through TikTok Shop. Data were collected using an online questionnaire distributed via Google Forms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLLS software. The results indicate that E-WOM, content marketing, and live streaming have positive and significant effects on brand trust and purchase decisions. Furthermore, brand trust significantly mediates the influence of E-WOM, content marketing, and live streaming on purchase decisions. Among the examined factors, live streaming demonstrates a strong contribution to enhancing consumer interaction and building brand trust. These findings highlight that online businesses can improve purchase intention and sales performance by strengthening brand credibility through positive customer reviews, engaging content strategies, and interactive live-streaming activities. This study contributes to social commerce and digital consumer behavior literature by emphasizing the strategic role of brand trust in shaping Generation Z purchasing decisions in digital marketplace environments.